2012
DOI: 10.1038/ng.2214
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome analysis of diverse Chlamydia trachomatis strains identifies phylogenetic relationships masked by current clinical typing

Abstract: Chlamydia trachomatis is responsible for both trachoma and sexually transmitted infections causing substantial morbidity and economic cost globally. Despite this, our knowledge of its population and evolutionary genetics is limited. Here we present a detailed whole genome phylogeny from representative strains of both trachoma and lymphogranuloma venereum (LGV) biovars from temporally and geographically diverse sources. Our analysis demonstrates that predicting phylogenetic structure using the ompA gene, tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
372
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 275 publications
(416 citation statements)
references
References 65 publications
36
372
0
3
Order By: Relevance
“…The genomes of nvCT serovar E strains E/SW2 and contemporaneous E/SW3 and E/SW4 have been described and published elsewhere (Harris et al ., 2012). When comparing nvCT strain E/SW2 and E/SW3, we previously showed that there were a total of 229 SNPs separating these two strains, 158 of which are found in a 30‐kb region spanning genes SW2 1391 (CTL‐393) to SW2 1601 (CTL‐417) (Harris et al ., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The genomes of nvCT serovar E strains E/SW2 and contemporaneous E/SW3 and E/SW4 have been described and published elsewhere (Harris et al ., 2012). When comparing nvCT strain E/SW2 and E/SW3, we previously showed that there were a total of 229 SNPs separating these two strains, 158 of which are found in a 30‐kb region spanning genes SW2 1391 (CTL‐393) to SW2 1601 (CTL‐417) (Harris et al ., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…When comparing nvCT strain E/SW2 and E/SW3, we previously showed that there were a total of 229 SNPs separating these two strains, 158 of which are found in a 30‐kb region spanning genes SW2 1391 (CTL‐393) to SW2 1601 (CTL‐417) (Harris et al ., 2012). This SNP‐dense region was shown to be a region of recombination and encompasses genes located alongside the plasticity zone or PZ.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations